Transrectal or transvaginal ultrasoundguided biopsy for pelvic masses: external validation and usefulness in oncologic patients - Won, So Yeon; Kim, Hyun-Soo; Park, Sung Yoon (Ultrasonography (Seoul, Korea), 2019)
The purpose of this study was to externally validate the diagnostic usefulness of transrectal ultrasound (TRUS) or transvaginal ultrasound (TVUS)-guided biopsy for pelvic masses, and to analyze the diagnostic performance of these methods in oncologic patients. A consecutive series of 30 patients who underwent TRUS- or TVUS-guided biopsy for pelvic masses was included. Tissue samples were obtained using an 18-gauge core biopsy needle under local anesthesia for lesions detected on computed tomography or magnetic resonance imaging. We analyzed the rates of diagnostic biopsies upon pathologic examination and biopsy-related major complications requiring treatment. In diagnostic biopsy cases, the performance was also investigated for all patients and patients with underlying malignancy. The diagnostic biopsy rate was 93.3% (28 of 30) for all patients and 95.0% (19 of 20) for oncologic patients. No patients had major complications. In diagnostic biopsies, the sensitivity, specificity, positive and negative predictive value, and accuracy for identifying malignancy were 100% (17 of 17), 72.7% (8 of 11), 85.0% (17 of 20), 100% (8 of 8), and 89.3% (25 of 28) for all patients and 100% (14 of 14), 60.0% (3 of 5), 87.5% (14 of 16), 100% (3 of 3), and 89.5% (17 of 19) for oncologic patients, respectively. This study externally validated the feasibility and safety of TRUS- or TVUS-guided biopsy. In addition, these techniques appear to enable accurate pathologic diagnoses of pelvic masses in oncologic patients to be made safely and relatively noninvasively.